PERANCANGAN RAK BUKU MULTIFUNGSI UNTUK TAMAN BACAAN MASYARAKAT DI KAMPUNG - Tania Hartono; Markus Hartono; Guguh Sujatmiko (Perpustakaan Universitas Surabaya, 2018)
Taman Bacaan Masyarakat is a government program to increase public reading, especially in Surabaya. Usually this Taman Bacaan Masyarakat is located in Kampung. The room used is the existing space in the village that can also mix with the hall. To improve the government has a program to make the villages in Surabaya became a village of literacy. The purpose of this paper is to design a furniture to support government programs so that it can be used in villages that have Taman Bacaan Masyarakat. The research method used is qualitative method. Through research using qualitative methods, it is known that the contents of the multifunctional bookshelf. From the results of the research, will be designed multifunction bookcase in the form of prototype that combines several functions in one unit. Equipped with promotional media, cost analysis designs to market reaction surveys. Thus, the use of this bookshelf supports the efficiency of space usage.